A mechanism for the fair division of climate change protection burdens - Carsten Helm (Fondazione Eni Enrico Mattei (FEEM), 1999)
Questions of burden sharing receive increasing attention in the climate change regime. This paper introduces the WESA-mechanism (WESA = Walrasian Equilibrium with the Stand Alone upper bound) for the fair division of common property resources and monetary compensations. Furthermore, the criterion of envy-freeness is adapted to the transferable utility context. The WESA-mechanism satisfies individual rationality, envy-freeness and the stand alone test, which follows as a minimum requirement from the resource and population monotonicity criteria, and thus compares favourably to the often advocated Walrasian mechanism. Finally, the WESA-mechanism will be applied to the fair division of climate protection burdens and illustrated quantitatively with a computable general equilibrium model. One of the central results is that developing countries should participate in emission reduction efforts in order to increase their global efficiency, but should be fully compensated for their incremental abatement costs.
Keywords: D63; Q20; H40; 330; Fair division; Climate change; Envy-freeness; Walrasian mechanism; Common property resources; Klimawandel; Umweltkosten; Gemeingüter; Allgemeines Gleichgewicht; Gerechtigkeit; Pareto-Optimum; Theorie; Welt